Patellofemoral osteoarthritis: how do patients behave? - Hernandez Peña , Victor Waldez; Marques Vidal , Juan Julio (Brazilian Journal of Implantology and Health Sciences, 2020)
Background: Patellofemoral osteoarthritis is detected in a large number of patients and is responsible for multiple symptoms and signs, among which pain predominates, its treatment is varied and ranges from conservative to surgical, in which the arthroscopic route stands out. Objective: Show the behavior of a group of patients with patellofemoral osteoarthritis. Material and methods: A descriptive observational study was carried out in 96 patients with the clinical and radiographic diagnosis of patellofemoral osteoarthritis from January 2015 to April 2017. The non-probabilistic and intentional sample consisted of 77 patients who met the selection criteria (inclusion and exclusion). Results: The average age was 52.2 years, the female sex, the right kneecap predominated and the cause that was most observed was primary. Pain during rest is one of its main manifestations. There is a correlation between the Iwano T and Outerbridge RE classification. In general, there are other affected compartments of the joint, the isolated presence is very rare, and arthroscopic treatment is very useful. Conclusions: Patellofemoral osteoarthritis is frequent, it generates symptoms and signs in a large group of patients. The presence of this condition is usually associated with other joint injuries, and patients can be treated arthroscopically.